2015
DOI: 10.1002/chem.201500978
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Transition‐Metal‐Catalyzed and Photopromoted Process: Synthesis of 2,3‐Fused 4‐Phenylnaphthalen‐1‐yl Carboxylates from 1,7‐Diaryl‐1,6‐diynes

Abstract: 2,3-Fused 4-phenylnaphthalen-1-yl carboxylates were synthesized in a step- and atom-economical manner using a ruthenium-catalyzed hydrocarboxylative cyclization of 1,7-diaryl-1,6-diynes and subsequent oxidative photocyclization. The scope of this novel two-step process was demonstrated by the construction of diverse structures from substrates with various tethers and terminal aryl groups. Late-stage CH functionalizations of the arylnaphthalene product further enhance the synthetic potential of the developed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Interestingly, however, when the deprotection reaction was run using cesium carbonate in DMF/H 2 O and left open to the air, in addition to the cleavage of the silyl ether, an unexpected oxidation also regiospecifically took place at the C9 position, resulting in transposition of the lactone carbonyl and generation of the C-ring type-I lactone 16 observed in other arylnaphthalene lignan lactone natural products including justicidin C. 59 The position of the lactone carbonyl in 16 was confirmed using a 1D Selective Gradient NOESY NMR experiment (Supplementary Information). Similar transformations resulting in the regioselective oxidation of arylnaphthalene systems have recently also been reported by Mondal et al 60 and Yamamoto et al, 51 with the type-I lactone being produced preferentially in both cases. Glycosylation of the free phenol of 16 , led to formation of compound 18 , containing the transposed carbonyl, but otherwise analogous to compound 6a .…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, however, when the deprotection reaction was run using cesium carbonate in DMF/H 2 O and left open to the air, in addition to the cleavage of the silyl ether, an unexpected oxidation also regiospecifically took place at the C9 position, resulting in transposition of the lactone carbonyl and generation of the C-ring type-I lactone 16 observed in other arylnaphthalene lignan lactone natural products including justicidin C. 59 The position of the lactone carbonyl in 16 was confirmed using a 1D Selective Gradient NOESY NMR experiment (Supplementary Information). Similar transformations resulting in the regioselective oxidation of arylnaphthalene systems have recently also been reported by Mondal et al 60 and Yamamoto et al, 51 with the type-I lactone being produced preferentially in both cases. Glycosylation of the free phenol of 16 , led to formation of compound 18 , containing the transposed carbonyl, but otherwise analogous to compound 6a .…”
Section: Resultssupporting
confidence: 77%
“…), and are calibrated using the residual undeuterated solvent peak (CDCl 3 : δ 7.26 ppm 1 H NMR, 77.16 ppm 13 C NMR; acetone-d 6 : δ 2.05 ppm 1 H NMR, 29.84 ppm 13 C NMR; DMSO-d 6 : δ 2.50 ppm 1 H NMR, 39.52 ppm 13 C NMR; CD 3 OD: δ 3.31 ppm 1 H NMR, 49.00 ppm 13 C NMR). As previously described by Charlton et al, 51 the hindered rotation of arylnaphthalene lignans about the C1’–C7’ bond results in observation of “additional” peaks in several 1 H and 13 C NMR spectra, an effect that appears to be highly solvent dependent. High resolution electrospray ionization mass spectra (HRMS-ESI) were recorded on a Thermo LTQ Orbitrap mass spectrometer.…”
Section: Experimentalsmentioning
confidence: 54%
See 1 more Smart Citation
“…In 2015, Shibuya et al . reported a combined transition‐metal‐catalyzed and photo‐promoted process for preparing hetero‐fused phthalan 56 (Scheme ).…”
Section: Synthetic Routes To Phthalansmentioning
confidence: 99%
“…Representative synthetic methodologies include intramolecular Diels–Alder type ring formation of arylpropiolic anhydride by Stevenson's group (Brown and Stevenson, 1964 , 1965 ; Maclean and Stevenson, 1966 ; Holmes and Stevenson, 1970 , 1971 ; Block and Stevenson, 1971 , 1973 ; Stevenson and Block, 1971 ; Stevenson and Holmes, 1971 ; Stevenson and Weber, 1989 , 1991 ; Anastas and Stevenson, 1991 ; Park et al, 2014 ), intermolecular Diels–Alder reaction of isobenzofurans and dimethyl acetylenedicarboxylate (De Silva et al, 1980 ; Plaumann et al, 1980 ), sequential Blaise reaction-intramolecular [4 + 2] reaction of 2-alkynylbenzonitriles (He et al, 2014 ), and Garratt–Braverman cyclization of substituted bis-propargyl ethers (Mondal et al, 2011 , 2012 ). Photo-assisted cyclization methods provide arylnaphthalene lignan lactones efficiently (Block and Stevenson, 1971 , 1973 ; Arnold et al, 1973 ; Yamamoto et al, 2015 ). Tandem conjugate addition-aldol reaction protocol (Ogiku et al, 1990 ; Kamal et al, 1994 ), benzoin condensation-thermal cyclization (Hayat et al, 2015 ), and electrophilic aromatic substitution protocols (González et al, 1978 ; Ogiku et al, 1995 ) have also been reported.…”
Section: Introductionmentioning
confidence: 99%